A study to assess clinical profile of Indian type 2 diabetes mellitus patients treated with Teneligliptin-ASPIRE study - Chadha, Manoj; Dhediya, Rajnish; Saxena, Gaurav; Naik, Swati Lad (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Teneligliptin is a DPP-4 inhibitor with unique chemical structure. Efficacy and safety of Teneligliptin is well established in the patients with type 2 diabetes mellitus (T2DM) in different randomized controlled trials. However, limited real-world data is available for Teneligliptin pertaining to Indian T2DM patient profile such as demographics, duration of disease, currently prescribed anti-hyperglycemic drugs, initiation of Teneligliptin as monotherapy or as an add on therapy. Methods: A cross-sectional, multicenter, non-interventional study was conducted to understand the demographics and clinical profile of Indian T2DM patients (n=5091) who were prescribed Teneligliptin. Results: Majority of patients were male (65.2%) with family history of T2DM present in 43.45% of cases. Age at onset of T2DM was 51.1±11.6 years. Among the T2DM patients, 36.2% of patients were newly diagnosed and more than half of them (54.7%) were uncontrolled with current anti-hyperglycemic drugs. Mean HbA1c level among these patients was 8.09±1.3%. Mean fasting and postprandial blood glucose levels were 170.2±46.9 mg/dl and 255.3±69.3 mg/dl respectively. Teneligliptin was prescribed as monotherapy in 2165 (41.66 %) of patients while as dual, triple and quadruple therapy in 2346 (46.08%) and 551 (10.82%) and 29 (0.56%) respectively. Among the patients on current anti-hyperglycemic treatment, most commonly prescribed drugs along with Teneligliptin were metformin (43.39%) followed by glimepiride (11%) and voglibose (3.42%). Conclusions: Teneligliptin is preferred as monotherapy and combination with metformin and sulfonylureas (mostly glimepiride) in newly diagnosed and uncontrolled T2DM patients in Indian scenario.